Racemization of Lactic Acid under Hydrothermal Conditions - Faisal, Muhammad; Saeki, Takashi; Daimon, Hiroyuki; Fujie, Koichi (Asian Journal of Chemistry, 2010)
The racemization mechanism of lactic acid was investigated under hydrothermal conditions at the temperature range of 250–350ºC and for a period of 30 min. Experiments were performed using a continuous flow tubular reactor made of SUS 316. Under the tested conditions, it was observed that pyruvic acid was formed as an intermediate, which subsequently transformed to both L- and D-lactic acids. The results suggested the hydrothermal racemization of L-lactic acid consists of consecutive-reversible reactions (i.e., L-lactic acid ↔ pyruvic acid ↔ D-lactic acid). The optical purity of L-lactic acid decreased with increasing reaction time and temperature. Further, the addition of NaOH slightly increased the purity of L-lactic acid.